Developing A Supplementary Book About The Potential and Utilization of Natural Resources for Social Studies Lesson - Wulandari, Ratna Fitri; Wahjoedi, Wahjoedi; Sudarmiatin, Sudarmiatin (Unversitas Negeri Malang, 2020)
Social studies subject is one of complex and broad lessons for students. This subject is considered as one of the most difficult subjects by students. This researcher, then, aims at developing a supplementary book to support the learning process of Social Studies. This research and development employed a modified Borg and Gall model (consisted of nine major stages). The assessment of the developed product was obtained from expert validators and field trials. The validation from the expert validators concluded that the developed supplementary book is feasible to be applied. In addition, the field trials confirmed that the developed supplementary book is practical to be used and it is able to improve students’ learning outcomes.